2013
DOI: 10.2214/ajr.12.9582
|View full text |Cite
|
Sign up to set email alerts
|

Large-Bore Nitinol Stents for Malignant Superior Vena Cava Syndrome: Factors Influencing Outcome

Abstract: Large-bore nitinol stents are highly effective for malignant superior vena cava syndrome. The survival rates of patients with caval vein stenosis due to either the primary tumor or secondary enlarged adenopathies were equal. An additional balloon-expandable stent was required in 22% of cases owing to incomplete expansion of the nitinol stent but was not associated with higher thrombosis rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(9 citation statements)
references
References 19 publications
2
6
0
Order By: Relevance
“…Comparisons of different clinical studies can be difficult, as there is inconsistent reporting of patient survival, clinical success, SVCS recurrence, stent type, and length of followup. However, all these studies showed high overall clinical success rates of 80%-95% with recurrence rates of 11%-28% for as long as 8 months of follow-up (8,12,21,24,25). Survival rate, technical success, clinical outcome, primary patency, and complications in the present study are all in agreement with data from the literature.…”
Section: Discussionsupporting
confidence: 91%
“…Comparisons of different clinical studies can be difficult, as there is inconsistent reporting of patient survival, clinical success, SVCS recurrence, stent type, and length of followup. However, all these studies showed high overall clinical success rates of 80%-95% with recurrence rates of 11%-28% for as long as 8 months of follow-up (8,12,21,24,25). Survival rate, technical success, clinical outcome, primary patency, and complications in the present study are all in agreement with data from the literature.…”
Section: Discussionsupporting
confidence: 91%
“…Wei et al believe that although stents combined with targeted drugs as secondary SVCS treatment for lung cancer cannot prolong the survival of patients, they can bene t patients [13]. In this study, the success rate of stent implantation technology was 100%, and all patients' clinical symptoms were signi cantly relieved after surgery, which is similar to the results reported by Mokry, Maleux and Fagedet [14,15,16].…”
Section: Discussionsupporting
confidence: 84%
“…Today, stent placement is typically done using conscious sedation and local anesthesia, and can be performed as long as the patient can lie flat or semi-supine on the operating table (Watkinson et al 2008 ; Charnsangavej et al 1986 ). Stent placement is quite effective for symptom relief, with up to 97–99 % of patients experiencing rapid post-operative relief (Maleux et al 2013 ; Gwon et al 2013 ). Headache is typically relieved immediately after the procedure, facial edema typically resolves within 24 h, and upper extremity and truncal edema may last for up to 72 h after stent placement (Hennequin et al 1995 ; Rosch et al 1992 ).…”
Section: Non-rt Treatment Modalitiesmentioning
confidence: 99%